Efektifitas Terapi Musik Terhadap Penurunan Kecemasan Pada Pasien Gagal Ginjal Kornik Yang Menjalani Hemodialisa di RSU Royal Prima Tahun 2025 - Wilda Hani Roully; Emanuel Giovan Kabeakan; Debora Angelina Gulo; Nursaida Purba; Tantri Sonia Manullang; Karmila Br Kaban (Universitas Pahlawan Tuanku Tambusai, 2025)
Background:Patients with chronic renal failure who receive hemodialysis treatment generally experience significant anxiety due to the long treatment process, discomfort, and lifestyle changes. Music therapy has been known to affect the autonomic and limbic nervous systems, potentially reducing anxiety. Purpose:The purpose of this study was to evaluate the effectiveness of using instrumental music in reducing anxiety in chronic renal failure patients undergoing hemodialysis procedures at RSU Royal Prima Medan in 2025. Method:The type of design applied in this research is quantitative quasi-experiment with pre test and post test measurement method without control group. A sample of 29 people was selected using accidental sampling technique. The intervention was instrumental music playback using earphones for 30-45 minutes every week. Anxiety measurement was carried out with the Hamilton Anxiety Rating Scale (HARS) at the pre- and post-intervention stages, then the results were analyzed through the Wilcoxon Signed-Rank test. Results:The results showed that before being given music therapy, most respondents (48.3%) experienced moderate anxiety levels. However, after the intervention, the majority of respondents (55.2%) no longer showed signs of anxiety. Based on the results of statistical tests, a p-value of 0.000 (p < 0.05) was obtained, which indicates a significant relationship between music therapy and anxiety reduction. Conclusion:Thus, it can be concluded that instrumental music therapy is effective in reducing anxiety in patients with chronic renal failure undergoing hemodialysis. This intervention can be used as a non-pharmacological alternative in nursing services to improve patient comfort and quality of life while undergoing hemodialysis therapy.